2015
DOI: 10.4238/2015.may.25.2
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin promotes T lymphocyte apoptosis in rats with severe acute pancreatitis via mitochondrial pathways

Abstract: ABSTRACT. We explored the influence of ulinastatin on apoptosis of T lymphocytes in rats with severe acute pancreatitis (SAP) and the effect of ulinastatin on mitochondrial apoptosis pathways in spleen lymphocytes. Thirty-six Wistar rats were randomly divided into three groups (N = 12): a sham operated group, a SAP group, and an ulinastatin-treated SAP group. The SAP model was established by injecting 5% sodium taurocholate into the intrapancreatobiliary duct. Study rats were sacrificed after 24 h, and splenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Another study indicated that ulinastatin can enhance immunological function and reduce the injury in SAP rats through inhibiting the apoptosis of CD4 + T cells [17]. Hao et al [18] showed that UTI can attenuate inflammatory response of patients undergoing cardiopulmonary bypass by inducing the expansion of CD4 + CD25 + Tregs.…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated that ulinastatin can enhance immunological function and reduce the injury in SAP rats through inhibiting the apoptosis of CD4 + T cells [17]. Hao et al [18] showed that UTI can attenuate inflammatory response of patients undergoing cardiopulmonary bypass by inducing the expansion of CD4 + CD25 + Tregs.…”
Section: Introductionmentioning
confidence: 99%
“…Ulinastatin can enhance immunological function and reduce the injury in SAP rats by inhibiting the apoptosis of CD4+ T cells. [11] Another study by Yu Pan et al in the rat model showed a significant decrease in CD4+CD25+ T cells in the ulinastatin group. [12] this study demonstrated that in the SAP rat model, pro-inflammatory cytokines TNF-α and IL-1α and anti-inflammatory cytokine IL-10 all were increased significantly, while TGF-α was decreased and treatment of ulinastatin led to decreased levels of TNF-α, IL-1α, and increased level of IL-10, thus attenuated the acute inflammatory response and improved the survival rate in the SAP rats.…”
Section: Population Characteristicsmentioning
confidence: 95%
“…A retrograde puncture was made on the biliary pancreatic duct via duodenal papilla. Subsequently, freshly prepared 5% sodium taurocholate solution (Sigma, USA) was perfused into the biliary pancreatic duct at 0.1 mL/min to reach an internal concentration of 0.1 mg/100 g as previously described (Wang et al, 2015b). The biliary duct was then clipped for 5 min to immerse all pancreatic lobes into sodium taurocholate solutions.…”
Section: Animal Modelmentioning
confidence: 99%